2017
DOI: 10.1177/0042098017736713
|View full text |Cite
|
Sign up to set email alerts
|

Integrating what and for whom? Financialisation and the Thames Tideway Tunnel

Abstract: The Thames Tideway Tunnel (TTT), often referred to as the Thames super sewer, is currently one of the largest infrastructure projects underway in any European city. Costing an estimated £4.2 billion, the sewer connects London's Victorian sewerage network with the Thames Wastewater Treatment Works at Beckton. The latter facility has been described as the UK's Water-Energy-Food nexus poster child, for its combination of desalination facilities, green energy generation and wastewater treatment. While physically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…A stark example of this process is the new £4.2 billion Super Sewer (the Thames Tideway Tunnel), eulogized as an engineering marvel akin to the finest achievements of Bazalgette in the Victorian era. As Loftus and March (2017) show, the super sewer can be read as a debt based incentive to charge customers excessive prices. Following the forensic financial investigation conducted by Pryke and Allen (2017), there are also clear parallels with the Carlsbad Desalination plant; a form of infrastructure geared towards bondholders in which financialisation has transformed a fixed infrastructure into liquid assets.…”
Section: Financialisation Of Water Revenue Streams and Infrastructurementioning
confidence: 99%
“…A stark example of this process is the new £4.2 billion Super Sewer (the Thames Tideway Tunnel), eulogized as an engineering marvel akin to the finest achievements of Bazalgette in the Victorian era. As Loftus and March (2017) show, the super sewer can be read as a debt based incentive to charge customers excessive prices. Following the forensic financial investigation conducted by Pryke and Allen (2017), there are also clear parallels with the Carlsbad Desalination plant; a form of infrastructure geared towards bondholders in which financialisation has transformed a fixed infrastructure into liquid assets.…”
Section: Financialisation Of Water Revenue Streams and Infrastructurementioning
confidence: 99%
“…Traditional responses to the problems that these arrangements bring are to add capacity to the piped networks to prevent overflows and reduce pollution from urban runoff. This is the principle for the new Thames Tideway Tunnel now under construction in London [25,37]; i.e. deal with the symptom as a problem, rather than using the opportunities the drivers (rainfall) provide.…”
Section: Traditional Water Managementmentioning
confidence: 99%
“…The various outputs from the Australian Water Sensitive Cities (WSC) programme demonstrate clearly the need to challenge the prevailing traditional water management culture [21,42] as potentially unaffordable (e.g. [14]) and also wasteful of opportunity [15,37]. It has also demonstrated that there is no single water management system that is invariably the most sustainable.…”
Section: Urban Flood Risk In a New Vision For Water Managementmentioning
confidence: 99%
See 2 more Smart Citations